PENGARUH KUALITAS PELAYANAN DAN FASILITAS KESEHATAN TERHADAP KEPUASAN PASIEN PADA PUSKESMAS LIMO KOTA DEPOK - Indah Widya Wardani; Budi Syamtoro (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to examine the influence of service quality and health facilities on patient satisfaction at the Limo Health Center, Depok City, both partially and simultaneously. The study employs a quantitative approach with probability/random sampling technique, where every member of the population has an equal chance of being selected as a sample. The study includes a sample size of 100 respondents. The research findings indicate that service quality (X1) and health facilities (X2) significantly influence patient satisfaction (Y), with a regression equation of Y = 11.570 + 0.313 (X1) + 0.329 (X2). The coefficient of correlation, indicating the strength of the relationship between the independent variables and the dependent variable, is 0.567, indicating a strong correlation. The coefficient of determination is 0,321, suggesting that service quality and health facilities influence on patient satisfaction in the amount of 32,1%, while the remaining 67,9% is influenced by other factors not examined in this study. Hypothesis testing obtained F count value > F table or (22,980 > 3,090), this is also strengthened by p value < Sig. 0.05 or (0.000 < 0.50). Thus, H0 is rejected and H3 is accepted. This shows that there is a significant simultaneous influence between service quality and health facilities on patient satisfaction at the Limo Health Center, Depok City.